First Aid Skill Improvement Assistance for Disaster Preparedness Volunteer Students - Indri Wahyuningsih; Risa Herlianita; Maya Iriyani (Jurnal Pengabdian Masyarakat Bestari, 2022)
The implementation of disaster management aims to guarantee the implementation of disaster management in a planned, integrated, coordinated and comprehensive manner in order to provide protection to the community from threats, risks and impacts of disasters. Student volunteers for disaster preparedness (Maharesigana) are formed as a forum for fostering and developing students in disaster risk reduction, community service in handling disaster preparedness, and carrying out disaster relief activities. The outcomes resulting from this community service activity are increasing the knowledge, understanding and skills of student volunteers for disaster preparedness in responding to medical emergencies through first aid measures, as well as the preparation of modules and practical guides in providing first aid for volunteers. The results of the dedication in the form of scientific articles are published in national journals and online mass media.